Antibiotic Effects on Microbial Communities Responsible for Denitrification and N2O Production in Grassland Soils - Semedo, Miguel; Song, Bongkeun; Sparrer, Tavis; Phillips, Rebecca L. (Frontiers in Microbiology, 2018)
Antibiotics in soils may affect the structure and function of microbial communities. In this study, we investigated the effects of tetracycline on soil microbial community composition and production of nitrous oxide (N2O) and dinitrogen (N2) as the end-products of denitrification. Grassland soils were pre-incubated with and without tetracycline for one-week prior to measurements of N2O and N2 production in soil slurries along with the analysis of prokaryotic and fungal communities by qPCR and next-generation sequencing. Abundance and taxonomical composition of bacteria carrying two genotypes of N2O reductase genes (nosZ-I and nosZ-II) were evaluated through quantitative PCR and metabolic inference. Soil samples treated with tetracycline generated 12 times more N2O, but N2 production was reduced by 84% compared to the control. In parallel with greater N2O production, we observed an increase in the fungi:bacteria ratio and a significant decrease in the abundance of nosZ-II carrying bacteria; nosZ-I abundance was not affected. NosZ-II-carrying Bacillus spp. (Firmicutes) and Anaeromyxobacter spp. (Deltaproteobacteria) were particularly susceptible to tetracycline and may serve as a crucial N2O sink in grassland soils. Our study indicates that the introduction of antibiotics to agroecosystems may promote higher N2O production due to the inhibitory effects on nosZ-II-carrying communities.